Abstraction level of van Hiele’s theory: Occurrence of side effects in GeoGebra integration - Kandaga, Thesa; Novianti, Idha; Adnan, Mazlini (Universitas Hamzanwadi, 2025)
One of the obstacles to teaching geometric transformation is the complex procedures that require a broad base of prerequisite knowledge. This complexity often leads students to focus on rote memorization and procedural calculations instead of understanding the underlying context. This study aims to overcome these challenges by developing a hypothetical learning trajectory (HLT) and using GeoGebra to enhance visualization and understanding. The case study involved ten university students in Indonesia who tackled the abstraction level in the Transformation, Isometries, and Reflection topics. The researchers analyzed students' worksheets, activity observations, and learning obstacle tests to extract their geometric thinking. Qualitative analysis of the data revealed that seven out of ten participants met three of the four abstraction level indicators. The use of GeoGebra in HLT helped overcome epistemological obstacles. However, integrating GeoGebra into the HLT introduced a new issue: a GeoGebra-centric habit characterized by an excessive dependence on GeoGebra in solving geometric transformation problems.